Bilateral Heschl’s gyrus display non-reciprocity in connectivity during the performance of simple arithmetic addition task - A. N. Yusoff; L. H. Te; S. Z. M. Mukari; A. I. Abd Hamid (Penerbit UKM, 2016)
Heschl’s gyrus (HG) is known to interact with other auditory related areas of the same hemisphere during the performance of an auditory cognitive task. However, the information about how it interacts with the opposite HG is still lacking. The aim of this study was to investigate the psychophysiologic interaction (PPI) between the bilateral HG during a simple arithmetic addition task and to verify the role of noise as an experimental factor that would modulate the PPI. Functional magnetic resonance imaging (fMRI) scans were performed on eighteen healthy participants, in which a single-digit addition task were solved during in-quiet (AIQ) and in-noise (AIN) conditions. The fMRI data were analysed using Statistical Parametric Mapping (SPM8). The interaction between the bilateral HG was investigated using PPI analysis. The response in right HG was found to be linearly influenced by the activity in left HG, vice-versa, for both in-quiet and in-noise conditions. The connectivity from right to left HG in noisy condition seemed to be modulated by noise, while the modulation is relatively small oppositely, indicating a non-reciprocal behavior. A two-way PPI model between right and left HG is suggested. The connectivity from right to left HG during a simple addition task in noise is driven by a higher ability of right HG to perceive the stimuli in a noisy condition. Both the bilateral HGs took part in the cognitive processes of arithmetic addition from which the interactions between the two were found to be different in noise.